Kajian Pengaruh Percepatan Waktu Pekerjaan Konstruksi Terhadap Biaya Proyek Bess Mansion Apartement Surabaya - Jaya, Adi Aprian; Yakin, Kusnul; Bustamin, Maulidya Octaviani (Universitas Dr. Soetomo, 2019)
In the implementation of construction project activities there are thre things that influence the success and failure of the project: time, cost and quality. The success of a project is usually seen from the timing of completion which is relatively short but without neglecting the quality of the project work. Appropriate and targeted project management and management are required to ensure the time, cost, and quality of the project. This is certainly to avoid a variety of undesirable things such as late settlement, swelling costs, quality failures, and so on that could have an impact on project failure and the emergence of the cost of fines. The purpose of this study is to calculate changes in cost and time of project implementation with alternatives to additional working hours (overtime) comparing the results between normal and cost changes after the addition of working hours (overtime). The data used in this research is secondary data obtained from contractor implementing. Arrow diagram The results program are critical paths and cost increases due to the addition of working hours (overtime) while the result of the time cost trade off method is the acceleration of duration and the increased cost due to the acceleration of duration in any accelerated activity. The results of this study indicate that the total project time and cost under normal conditions is 508 days at a cost of Rp 22.240.655.701 Â with the addition of 3 hours of overtime work in the duration of crashing 485 days and at a cost of Rp 23.252.220.373,34